2017
DOI: 10.1002/stem.2726
|View full text |Cite
|
Sign up to set email alerts
|

The Pericytic Phenotype of Adipose Tissue-Derived Stromal Cells Is Promoted by NOTCH2

Abstract: Long-term diabetes leads to macrovascular and microvascular complication. In diabetic retinopathy (DR), persistent hyperglycemia causes permanent loss of retinal pericytes and aberrant proliferation of microvascular endothelial cells (ECs). Adipose tissue-derived stromal cells (ASCs) may serve to functionally replace retinal pericytes and normalize retinal microvasculature during disease progression. We hypothesized that Notch signaling in ASC underlies regulation and stabilization of dysfunctional retinal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…A soft hydrogel is also easier infiltrated by host cells like ASC and endothelial cells than stiff hydrogels. In this way, both ASC and endothelial cells can stimulate angiogenesis inside the hydrogel, which might result in increased wound healing rates (Terlizzi, Kolibabka, Burgess, Hammes, & Harmsen, 2017). It remains to be determined whether the stability and longevity of these hydrogels supports cells' maintenance, migra- ECM, which results in more cross links between proteins and therefore a high stability of the ECM proteins (Voziyan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A soft hydrogel is also easier infiltrated by host cells like ASC and endothelial cells than stiff hydrogels. In this way, both ASC and endothelial cells can stimulate angiogenesis inside the hydrogel, which might result in increased wound healing rates (Terlizzi, Kolibabka, Burgess, Hammes, & Harmsen, 2017). It remains to be determined whether the stability and longevity of these hydrogels supports cells' maintenance, migra- ECM, which results in more cross links between proteins and therefore a high stability of the ECM proteins (Voziyan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ASCs contribute to repair by differentiation into parenchymal or stromal cells, such as smooth muscle cells, pericytes, fibroblasts, adipocytes or osteoblasts, depending on the damaged tissue [8]. We have shown that ASCderived pericytes both promote and stabilize vascularization in vitro and in vivo in a NOTCH2-dependent fashion [10,11]. In these studies, we also cultured ASCs in 3D matrices of commercial extracellular matrix i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested a direct role for ASCs in retinal microvascular support [ 16 ]. In rodent models of diabetic retinopathy, ASCs acquired pericytic features, which dampened proliferative angiogenesis [ 17 , 18 ]. Recently, we showed that the pericytic nature of ASCs depends on neurogenic locus notch homolog protein 2 (NOTCH2)-based juxtacrine interaction between ASCs and endothelial cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%